KETERKAITAN PERBANDINGAN KINERJA PANEL SURYA DALAM SITUASI LINGKUNGAN TERTENTU DENGAN MEMANFAATKAN SIRKUIT SENSOR - Siagian, Ade Onny; Prasetyo, Trisna Fajar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
This research is to find out solar panels produce electric current depending on the intensity of sunlight. In addition, temperature, humidity and other environmental parameters affect the energy conversion process. Commercial solar panels are widely available in the market. The price depends on the selling capacity of diesel as well as the materials that determine the performance of the power plant. This paper compares monocrystalline and polycrystalline solar panels using a sensor circuit. The impact of environmental parameters on solar panels is also assessed. The results show that monocrystalline outperforms polycrystalline. The voltage, current and output power of monocrystalline were 2.8%, 7.73% and 6.41% higher than polycrystalline. Monocrystalline solar panels are also more stable to environmental changes. This is how the stability of efficiency.